ANALISIS TEMPERATUR PADA PROSES TERBENTUKNYA BAHAN BAKAR MINYAK (BBM) DENGAN METODE PIROLISIS PADA PROTOTYPE ALAT PENGOLAH LIMBAH PLASTIK MENJADI BBM - Dawi Yanti; Adelia Rohani; M Saleh; Mohammad Lutfi (Sekolah Tinggi Teknologi MIGAS, 2022)
The physical properties of plastic waste that is not easily biodegradable is a serious problem in pollution on land and at sea. Therefore, technology to be able to solve these problems needs to be developed. This study aims to understand at what temperature plastic waste can produce fuel oil. The type of waste used in this research is polyethylene terephthalate (PET), which is a type of plastic that uses drink bottles. The design of the device to convert plastic into fuel oil in this study consisted of 3 components, namely a valve which functions to regulate the flow of steam from the reactor tube to the condensate tube, the temperature gauge functions to measure the temperature contained in the reactor tube, and the heat blanket functions as a coating, this can reduce excessive heat in the reactor tube. The results revealed that at a temperature of 100ºC to 150ºC with a variation of time (26.3, 27.3, and 28) minutes did not produce oil. At a temperature of 200ºC to 250ºC with time variations (33, 34, and 35) minutes, the condensate tube begins to produce fuel above the water surface.